Pengaruh Pemberian Kerupuk Singkong Ebi terhadap Perubahan pH Saliva pada Anak Balita Stunting - Annisa, Nurul; Ernita, Lisa; Minarti, Minarti; Bayu Argaheni, Niken; Arfiah (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Stunting in toddlers can increase the risk of dental caries due to disruptions in salivary gland growth caused by the shrinkage of salivary glands resulting from oral cavity conditions and reduced saliva flow. This study aims to evaluate the influence of cassava chips with shrimp (ebi) consumption on saliva acidity levels in stunted toddlers in the Work Area of Pekkae Health Center, Barru Regency. Methods: The research method used a Pretest-Posttest Control Group Design, with two randomly selected groups given a pretest to determine the initial conditions and any differences between the experimental and control groups. The study population included all stunted toddlers in the Work Area of Pekkae Health Center, totaling 190 toddlers, and the sample was selected based on inclusion criteria, including toddlers experiencing stunting, aged 36-59 months, having teeth, able to participate in the intervention, without allergies, and able to follow the cassava chips with shrimp (ebi) feeding schedule. A total of 32 toddlers were selected using purposive sampling. The statistical test used was the Wilcoxon test. Results: The research results showed significant findings in saliva acidity levels in Week 1 (Asymp. Sig. [2-Tailed] = 0.002), Week 2 (Asymp. Sig. [2-Tailed] = 0.001), Week 3 (Asymp. Sig. [2-Tailed] = 0.003), Week 4 (Asymp. Sig. [2-Tailed] = 0.002), and Week 5 (Asymp. Sig. [2-Tailed] = 0.001). The overall Asymp. Sig. (2-Tailed) value was 0.003, indicating a significant change before and after the consumption of cassava chips with shrimp (ebi). Conclusion: The conclusion of this study is the influence of cassava chips with shrimp (ebi) on changes in saliva pH in stunted toddlers. It is hoped that the general public, especially parents, will prioritize the oral health of toddlers